Argimou : a legend of the Micmac - Huyghue, S. Douglass S., 1816-1891 (Early Canadian literature series., 2017)
"It's a reprint of a novel that appeared originally in serial form in 1842, and it tells of the fall of Fort Beausejour and the expulsion of the Acadians. But it's essentially an adventure story and a captivity tale, and it's also a denunciation of the marginalization of Indigenous culture in the face of European colonial expansion."--